Предмет: Математика, автор: Аноним


умоляю решите пожалуйста

Приложения:

Ответы

Автор ответа: maksyakup
1

Ответ:

208\\2) 6-3(x+1)=7-2x\\6-3x-3=7-2x\\-3x+2x=7-3\\-x=4\\x=-4\\3) (8x+3)-(10x+6)=9\\8x+3-10x-6=9\\-2x=9+3\\x=12:(-2)\\x=6\\6)\frac{3}{5} (\frac{7}{9}x-\frac{1}{3}) =x-2\frac{1}{3}\\  \frac{3}{5} *\frac{7}{9}x-\frac{3}{5} *\frac{1}{3}+x=-2\frac{1}{3}\\\frac{7}{15}x+x=  -2\frac{1}{3} + \frac{1}{5} \\1\frac{7}{15}x= -\frac{32}{15}\\ x=-\frac{32}{15}*\frac{15}{22}\\x=-\frac{16}{11}\\ x=-1\frac{5}{11}

209.\\1) 8(5-3x)=6(2-4x)+7\\40-24x=12-24x+7\\-24x+24x=19-40\\Net|resheniy\\2) 5(x-12)=6(x-10)-x\\5x-60=6x-60-x\\5x-5x=-60+60\\0=0\\Net|resheniy

Пошаговое объяснение:

Похожие вопросы